2011
DOI: 10.1002/maco.201106072
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of CuCrFeNiMn high entropy alloy system in 1 M sulfuric acid solution

Abstract: The high pressure torsion (HPT) process was used to process the FeNiCoMoV high-entropy alloy. The open-circuit potential test, the potentiostatic polarization curve test and the electrochemical impedance spectroscopy were used to study the effect of corrosion behavior of FeNiCoMoV High Entropy Alloy in 1M NaOH Solution. The results show that the grain refinement of FeNiCoMoV alloy is significant after 6 cycles of high pressure torsion, the phase structure has not changed and the electrochemical impedance of HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…Several researchers have explored the influence the effect of copper (Cu) on the corrosion and electrochemical response of CCAs. [58][59][60] Hsu et al 58 investigated the corrosion behaviour of the FeCoNiCrCu x system (with x taken as 0, 0.5 and 1) in 0.6 M NaCl and observed that increasing Cu content resulted in a higher i corr , lower E corr and lower E pit values for this system (Fig. 8c).…”
Section: The Influence Of Different Alloying Elements On the Corrosiomentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have explored the influence the effect of copper (Cu) on the corrosion and electrochemical response of CCAs. [58][59][60] Hsu et al 58 investigated the corrosion behaviour of the FeCoNiCrCu x system (with x taken as 0, 0.5 and 1) in 0.6 M NaCl and observed that increasing Cu content resulted in a higher i corr , lower E corr and lower E pit values for this system (Fig. 8c).…”
Section: The Influence Of Different Alloying Elements On the Corrosiomentioning
confidence: 99%
“…The effect of Cu on the corrosion of the CuCrFeNiMn system was also investigated by Ren et al 59 using immersion tests and potentiodynamic polarisation tests in 1 M H 2 SO 4 . The CuCr 2 Fe 2 -Ni 2 Mn 2 alloy with a low Cu content and minimal elemental segregation had the highest corrosion resistance, whereas the Cu 2 CrFe 2 Ni 2 Mn 2 alloy with the higher Cu content and more substantial elemental segregation had the poorest corrosion resistance.…”
Section: The Influence Of Different Alloying Elements On the Corrosiomentioning
confidence: 99%
See 1 more Smart Citation
“…Signs of corrosion can be observed in the Al-Ni-rich BCC phase, according to the surface morphology of the alloys after the immersion tests. Ren et al studied the influence of the Cu addition on the corrosion behavior of the CoCrFeNiCux alloy in the 1 M H2SO4 [48]. Similar to the case in the NaCl solution, due to the segregation of Cu, the interaction between the Cu-rich, Cr-depleted inter-dendrite and the Cr-rich, Cu-depleted dendrite led to galvanic corrosion.…”
Section: Corrosion Behavior In Acid Solutionsmentioning
confidence: 99%
“…The addition of Mo improved the corrosion resistance in the NaCl solution (as mentioned above) but impacted the corrosion behavior in the H2SO4 solution. The reason is that according to the Pourbaix diagram [49], the formation of the protective molybdenum species on the surface is impossible when considering the 0.5 M H2SO4 acid Ren et al studied the influence of the Cu addition on the corrosion behavior of the CoCrFeNiCu x alloy in the 1 M H 2 SO 4 [48]. Similar to the case in the NaCl solution, due to the segregation of Cu, the interaction between the Cu-rich, Cr-depleted inter-dendrite and the Cr-rich, Cu-depleted dendrite led to galvanic corrosion.…”
Section: Corrosion Behavior In Acid Solutionsmentioning
confidence: 99%